Total hip arthroplasty using TRI-LOCK® DePuy bone preservation femoral stem: our experience - Sperati, G.; Ceri, L. (Acta Biomedica Atenei Parmensis, 2014)
Purpose: in this study we report our 3-years experience (from January 2010 to December 2013) of 101 total hip arthroplasties using Tri-Lock® DePuy bone preservation femoral stem, all performed in our clinic. Methods: 101 patients (F54-M47; median age around 69 yrs, range 42-84 yrs). 51 arthroplasties were implanted on the right side whereas 50 on the left side. The average follow-up was 27,3 months. All the arthroplasties were coupled with Pinnacle® polyethylene acetabular cup system; 98 prostheses were implanted cementless whereas cement was used in 3 cases. Results: the Tri-Lock® femoral stem allows both soft tissues and bone stock preservation, leading to greater trochanter maintenance, less spongy bone removal and distal cavity bone tissue conservation. In our experience, we were able to implant the Tri-Lock® femoral stem even in osteoporotic and overweight patients using Gription® porous coating. This allowed for commencing an intensive rehabilitation program with stable load from the following day, without observing any early complications or loosening. Conclusions: according to us, this device is solid and safe, providing remarkable sparing of both soft tissues and bone stock.